PROTOTIPE SMART GUIDANCE STICK TUNANETRA BERBASIS ARDUINO DENGAN SENSOR HC-SR04 SEBAGAI PROJEK DALAM PEMBELAJARAN DIGITAL: Prototype of an Arduino-Based Smart Guidance Stick for the Visually Impaired Using an HC-SR04 Sensor: A Digital Learning Project - Riswanto Riswanto; eko prihandono; Arif Hidayat; Wisnu Rifky Alfathir Riswanto (Universitas Muhammadiyah Metro, 2025)
This study presents the design, development, and evaluation of a Smart Guidance Stick (SGS) that enables visually impaired children to navigate safely while serving as a hands-on digital-learning project for university students. Following the ADDIE R&D framework, researchers analysed user needs, designed an Arduino-based prototype integrating an HC-SR04 ultrasonic sensor, buzzer, lightweight cane body, and battery pack, then built, implemented, and refined the device. Thirty experimental trials conducted with child users in both indoor and outdoor settings produced a mean absolute distance error of 1.13 cm (SD = 0.84 cm) and 80 % detection accuracy for a ≤2 cm error threshold, fulfilling the <3 cm safety margin widely accepted for mobility aids. Although performance trails advanced dual-sensor canes reported in recent literature, SGS offers a low-cost, single-sensor alternative suitable for classroom fabrication. Pedagogically, the project embodies project-based learning principles: students apply coding, electronics, and CAD skills while cultivating empathy and digital literacy through co-design with disabled stakeholders. The hybrid learning mode delivered via the SPADA UM Metro LMS further illustrates inclusive digital education practice. Comparative analysis with prior studies highlights avenues for improvement sensor redundancy, signal-filtering algorithms, GPS or IoT modules, and expanded user experience tests to raise accuracy above 90 % and extend battery life beyond five hours. Overall, SGS demonstrates how affordable assistive technology can enhance blind learners’ autonomy and simultaneously act as a rich instructional object, modelling the integration of engineering design, social responsibility, and accessibility within higher-education curricula